Patterns of Electronic Mail Discourse in Two Malaysian Organisations - Habil, Hadina (2003)
This study investigates the patterns of email discourse in workplace communication. Email exchanges are analysed in order to explicate how members of an organisation interact through email to meet the specific communicative needs of the organisation. It is the assumption of this study that email discourse represents social action of members in the organisation and it is part of a social practice. The linguistic data for the study consists of email texts and the study emulates the language in context model. The three parameters of the field, mode and tenor that constitute register, are investigated to provide insight on what the participants are engaged in, the people involve in the interaction and on the role the language plays. The data is analysed in two parts: text-based features and text in context. The text-based features is further divided into two: the micro and macro analyses. The macro analysis involves looking at the surface and content structure of email messages. This analysis provides information on the generic structure of email. The micro analysis involves eliciting empirical evidence from the corpus by using concordancing tools. A textual analysis is also carried out to draw the textual features and lexical choices and expressions used by writers in the emails. The text in context constitutes the interpretation and explanation of the reason why and the explanation of how certain linguistic features are adopted in some situation, when communicating with certain people to achieve certain communicative purposes. Examples of email messages are discussed and the various strategies are explained based on the linguistic data, and the social context in which the emails are written. Reference to the specific organisational culture and practices are formulated. The evidence shows that in the context of workplace communication, the available linguistic resources are used creatively and purposively via email in meeting the specific communicative purposes of members of organisations. The social, political and cultural aspects of the interaction influence the way emails are written and email writers are consciously aware of the available resources. The study concludes that people in organisation adopt various discourse and rhetorical strategies to meet the specific communicative needs at the workplace. The strategies selected reflect the writers' interpersonal relationship with their email interactants while the linguistic realisation in the email texts manifest the values they hold as members of the organisation. Finally, a model of factors influencing the construction of the email messages at the workplace and a taxonomy of the linguistic features and rhetorical strategies in email as an institutional genre are posited which provide a framework for future research in the field.